Novel Dioxolan Derivatives of Indole as HIV‐1 Integrase Strand Transfer Inhibitors Active Against RAL Resistant Mutant Virus. Issue 17 (25th October 2016) - Singh, Raja; Yadav, Pooja; Urvashi,; Tandon, Vibha
Abstract: Drugs have been discovered to treat HIV‐1 but mutation in virus causing resistance to drug, necessitates a continuous development of novel molecules. We have developed new chemical constructs that target HIV‐1 integrase (HIV‐IN) and it's mutant. We have evaluated 22 dioxolan and malonyl derivatives of indole. It was observed that C‐3 substituted dioxolan derivatives13 c and13 o exhibited outstanding strand transfer inhibitory activity with IC50 at 5.7 and 0.2 μM respectively. The therapeutic index of13 o was comparable to raltegravir (RAL). Compounds13 c and13 o not only showed excellent antiviral activity (EC50 ) in wild type, a moderate activity was also observed against mutant IN i. e. G140S (4.7 and 0.2 μM) and Y143R (5.0 and 0.37 μM) respectively. The computational study suggested that these inhibitors bind centrally at the active site of integrase making a close contact with the residues in or around the active site of wild type and mutant proteins. Thus the newly synthesized dioxolan derivatives opened the possibility for development of more effective IN inhibitors exploiting the strategy mentioned in our paper. Abstract : Based on C‐3 substitution dioxolan and malonyl derivatives of indole has been described in which two molecules gives excellent HIV‐IN strand transfer inhibitory activity and also shown good inhibitory activity against mutant IN protein G140S and Y143R.